Determination of tribological and mechanical properties of SnPbCuSb (white metal) bearings - Ünlü, B.S. (Фізико-хімічна механіка матеріалів, 2010)
White metals (SnPbCuSb) are widely used as journal bearing materials for tin and lead based alloys. In this study, tribological and mechanical properties of these journal bearings manufactured from Sn based SnPbCuSb, pure Sn, pure Pb bearings and from alloy elements, pure Cu metals were determined. SAE 1050 steel shaft (journal) was used as a counter abrader. Wear experiments were carried out in every 30 min for the total of 150 min by using radial journal bearing wear test rig. It was shown that the lowest friction coefficient of bearing and journal wear loss occurred in SnPbCuSb alloyed bearing.